Ketidakefektifan Kalimat Pada Wacana Dalam Buku Paket Mandiri Bahasa Indonesia Untuk Smp/Mts Kelas Vii - Futih, Febriarni Fatiha Falahallaily; , Prof. Dr.Markhamah, M. Hum (2016)
ABSTRACT Febriarni Fatiha Falahallaily Futih/A310120192. INEFFECTIVENESS SENTENCE ON SELF DISCOURSE IN BOOK PACKAGE FOR INDONESIAN SMP / MTS CLASS VII. Research Paper. Faculty of Teacher Training and Education, Muhammadiyah Surakarta University. November, 2016. Textbooks are teaching materials most widely used among all other teaching materials. In the book self-contained package discourse into Indonesian teaching materials class VII. This discourse will be read by students every day. Indirectly learners will assume that literary discourse is read correctly. In fact, the average author cites lack of attention to the discourse. The purpose of this study is to analyze and describe the ineffectiveness of a single sentence and a compound contained in the discourse in textbooks Indonesian independently for SMP / MTs class VII. This type of research is descriptive qualitative research. The data in this study is a sentence in the existing discourse in textbooks Indonesian independently with no or less effective. Data collection techniques in this study is the engineering documentation and record. Based on the data that has been analyzed, it was found two groups, the ineffectiveness of a single sentence 83.02% with details based on usage of the word said 33.96%, 11.32% logical errors, redundancy 20.75%, 7.55% inaccuracy meanings of words, sentences ambiguous 1.89%, 3.77% ineffectiveness form of words, the influence of local languages 1.89%, 1.89% wastefulness words, the ineffectiveness of the second group 16.9% compound sentences with conjunctions imprecision details by 9.43%, the use of conjunctions excess 3.77%, 1.89% conjunctions removal, and the vagueness of the core elements of the sentence by 1.89%. Analysis of the ineffectiveness of this sentence can become a reference of learning and add to the discourse examples of the effectiveness of the sentence. The existence of this analysis as well as an effort evaluation; UASI author of textbooks in decision discourse. Keywords: Textbooks, ineffectiveness sentences, simple sentences, compound sentences.